2020
DOI: 10.3390/ijerph17072181
|View full text |Cite
|
Sign up to set email alerts
|

See, Like, Share, Remember: Adolescents’ Responses to Unhealthy-, Healthy- and Non-Food Advertising in Social Media

Abstract: Media-saturated digital environments seek to influence social media users’ behaviour, including through marketing. The World Health Organization has identified food marketing, including advertising for unhealthy items, as detrimental to health, and in many countries, regulation restricts such marketing and advertising to younger children. Yet regulation rarely addresses adolescents and few studies have examined their responses to social media advertising. In two studies, we examined adolescents’ attention, mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 70 publications
(81 reference statements)
9
119
0
4
Order By: Relevance
“…The internet also consists of the use of social networks. The use of social networks has been shown to change the way that consumers search for information and select products; they are becoming prominent sources of information, including for food choices (see [ 43 , 44 ], for example). From this perspective, social media can influence information strategies in two ways: Reducing the cost of releasing information, compared to that of traditional mass media (i.e., television or radio), and making specific consumer groups more easily targeted.…”
Section: Discussionmentioning
confidence: 99%
“…The internet also consists of the use of social networks. The use of social networks has been shown to change the way that consumers search for information and select products; they are becoming prominent sources of information, including for food choices (see [ 43 , 44 ], for example). From this perspective, social media can influence information strategies in two ways: Reducing the cost of releasing information, compared to that of traditional mass media (i.e., television or radio), and making specific consumer groups more easily targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Although teens are increasing in agency and autonomy and are certainly well versed in the techniques used by advertisers in these important social spaces, they are not immune to the powerful impact of marketing, and this is particularly the case online. Advertising online, including food marketing, targets adolescents specifically, drawing successfully on their social-developmental needs for connection with peers, working under the radar to activate emotional, identity-laden responses and build long-lasting relationships with brands [ 35 , 36 , 71 , 72 , 73 ]. Buchanan and colleagues [ 74 ] note that “earned” social media advertising (forwarded by users within networks—see Box 1 ) is believed to have the most detrimental effects on young consumers, as this form of marketing is no longer clearly commercial, and can be disguised as a post by the user.…”
Section: Discussionmentioning
confidence: 99%
“…Unhealthy food brands can also play a role in adolescents’ social relationships and identity creation: Murphy and colleagues [ 71 ] found that teens prefer social media HFSS advertising posts to those for healthy items or non-food items and are more likely to share, or judge a peer positively, if HFSS advertising posts are in their feed.…”
Section: Discussionmentioning
confidence: 99%
“…The digital environment within which children encounter alcohol, unhealthy food and gambling marketing is complex and pervasive. The effect of marketing is cumulative: repeated exposure to marketing of harmful products leads to increased recall and recognition of brands by children, and ultimately increased purchase and consumption of these products, 58 whether through 'pester power' for unhealthy food or through purchase by teenagers themselves who have gained their independence. Children are more susceptible to marketing messages the younger they are, 59 and their exposure to harmful products and behaviours in the digital environment helps to drive new and harmful social norms.…”
Section: Harmful Industries Marketing: a Joined-up Approachmentioning
confidence: 99%
“…• A quarter of celebrity endorsements of products on social media are for unhealthy foods -and children are more likely to share these posts than posts for healthier products. 67…”
Section: Alcoholmentioning
confidence: 99%